(untitled) (Archive of Conferences, 2021)
This article was teaching in secondary schools students in the fine arts tabaqalashtirib and creative development, and the ability of school teachers would be thoroughly differentiated scientific bases of art education, training tabaqalashtirib great effect, as well as the availability of its complex aspects of lighting.